The Role of Parents in Fostering Student Learning Motivation - Muda'im, Syarifah; Shanie, Arsan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to explain the role of people in fostering the learning motivation of grade V students of MI NU 11 Karangayu Cepiring. This research is qualitative with a case study approach. Research data in the form of the role of parents in fostering student motivation with parent and student data sources. Data collection techniques are carried out by observation, interviews, and documentation. At the same time, data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the role of parents in fostering children's learning motivation (students) included giving praise, giving attention, giving advice, giving gifts, giving punishments, and providing learning facilities. Thus, the character of children (students) to study becomes more active because they have a parent figure who can encourage and motivate them to be better.